PERAN MEDIA SOSIAL INSTAGRAM DALAM PEMBENTUKAN IDENTITAS DIRI REMAJA - Septiana, Wiwit Cahya; Nurito, Nurito; Amelia, Helen Putri; Setiyoko, Didik Tri (FKIP Universitas Al Washliyah Medan, 2025)
This research discusses the role of Instagram in the process of forming self-identity in adolescents. As a visual-based platform, Instagram provides a space for individuals to express themselves, where users can build, create, modify and present their work to a wide audience. The main aim of this research is to examine how social media, especially Instagram, contributes to the formation of teenagers’ self-identity using a literature review method. This type of research focuses on reviewing relevant articles regarding the role of Instagram in the formation of adolescent identity, which were published in scientific journals between 2012 and 2024. The selection of articles was carried out based on the theory of symbolic interaction which is the basis of the study. The research results show that Instagram plays a significant role in supporting the process of adolescent identity formation. This role includes facilitating the exploration of self-identity, strengthening the relationship between self-identity and society, as well as the function of Instagram as a connecting media that helps teenagers develop their self-identity better and more broadly.